Progressive Hemifacial Atrophy with Morphea of Cheek - Ajit Auluck; Keerthilatha M Pai (Wolters Kluwer Medknow Publications, 2006)
Scleroderma is a rare collagen disorder in which fibrosis of skin, subcutaneous tissues and muscles can occur with occasional involvement of bones. Localized scleroderma is a benign condition but can cause significant deformity when it affects the face. We report a case of localized scleroderma of the face causing progressive hemifacial atrophy.